Retropancreatic Nerve Plexus Hanging Maneuver for Pancreatoduodenectomy for Cancer of the Head of the Pancreas. Issue 5 (May 2023) - Chiba, Naokazu; Ochiai, Shigeto; Gunji, Takahiro; Kobayashi, Toshimichi; Hikita, Kosuke; Sano, Toru; Tomita, Koichi; Kawachi, Shigeyuki
The efficacy of the hanging maneuver for the retropancreatic nerve plexus (RNP) to enhance the confirmation of the margin status and to facilitate en-bloc resection for pancreatoduodenectomy is studied. The exit of the hanging maneuver of the RNP is the left part of the superior mesenteric artery, and the entry is the cranial part of the celiac axis. The entry of the hanging maneuver was connected to the dissection line on the right side of the celiac axis. Thereafter, the tape of the hanging maneuver was pulled to the right side, and the RNP was deployed widely. Finally, the RNP was easily dissected using a sealing device other than inferior pancreaticoduodenal artery. With the correct implementation of the hanging maneuver, we believe that it would be possible to obtain reliable R0 resection as well as a reduction in blood loss and operation time.